Development of E-Module Based on Discovery Learning to Improve Students' Learning Outcomes in PKKR Subject for Grade XI TKRO at State Vocational High School 1 Merbau - Nur Kholistiyawatin; Hasan Maksum; Waskito; Wawan Purwanto (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to develop, measure the validity, assess the practicality, and evaluate the effectiveness of an e-module based on discovery learning to enhance the learning outcomes of 11th-grade students in Electrical Vehicle Maintenance subject. This study falls under the category of Research and Development, involving the development of an e-module for the topic of light vehicle electrical maintenance that is valid, practical, and effective using the discovery learning approach. The development of this e-module based on discovery learning follows the 4-D model, which includes defining, designing, developing, and disseminating stages. The validation results of the developed e-module based on discovery learning fall under the category of valid. The practicality assessment of the discovery learning-based module is classified as very good, and the effectiveness of the e-module based on discovery learning as a learning media indicates that this learning media is considered effective.